Financial Literacy and Income as Determinants of Digital Financial Application Usage Among Millennials - Gami, Emelia Rahmadany Putri; Mardhiyah, Ainun; Muda, Iskandar (Journal of Economic Education and Entrepreneurship Studies, 2025)
Digital financial applications have become essential tools for transaction management, savings, payments, and investment activities, particularly among millennials who represent the highest adoption segment in the digital economy. This study examines the influence of financial literacy and income on digital financial application usage behavior among millennials. A quantitative explanatory design was employed, and data were collected from active users of digital financial platforms, including mobile banking, e-wallets, and online investment services. The dataset was analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS) to assess both the measurement and structural components of the model. The measurement model exhibited strong reliability and validity, supported by high factor loadings, Composite Reliability values exceeding 0.89, and Average Variance Extracted (AVE) values above 0.73. Discriminant validity was confirmed through the Fornell–Larcker criterion and HTMT analysis. The structural model revealed that financial literacy significantly influences digital financial behavior (β = 0.389, t = 6.214, p < 0.001), emphasizing the role of knowledge, attitudes, and financial management capability in shaping responsible digital financial engagement. Income also demonstrated a significant positive effect (β = 0.334, t = 5.102, p < 0.001), indicating that greater economic capacity supports broader and more advanced use of digital financial tools. The model’s R² value of 0.472 indicates moderate predictive power, while a Q² value of 0.311 confirms strong predictive relevance. These findings underscore the importance of both cognitive and economic factors in cultivating safe, inclusive, and sustainable digital financial behavior among millennials.